Monitorização intensiva de reação adversa a medicamentos em pacientes hospitalizadas em Fortaleza-Ceará - Sousa, Mariana de Oliveira Brizeno de (2004)
The large use of oxacillin in Brazilian hospitals and the ausence of scientific data confirming its safety, justify the necessity of carrying out well –structured studies, identifying the existence of possible triggering factors of the reactions. AIM: To study the use of oxacillin and the occurrence of adverse reactions in two different groups, identifying risk factors associated. METHODS: Children using oxacillin were monitorized from October 2000 to July 2001 in the Universitary Hospital Walter Cantídio (HUWC), as well as ones under treatment with oxacillin of block D from Children’s Hospital Albert Sabin in the period of July 2001 and March 2002 (FIRST STUDY). Also, patients under treatment with oxacillin from HUWC, during the period of July until October 2003, were followed up (SECOND STUDY). The follow-up was done through daily visits in the infirmary and analysis of medical records and prescriptions, being observed the clinical history, prescribed drugs, laboratorial exams, oxacillin use, adverse reaction reports related to oxacillin (AROx) and procedures done due to these AROx. The reactions were reported and classified according to causality and gravity (both studies) and hypersensitivity type (in the SECOND STUDY). Statistical tests were used promptly. RESULTS: FIRST STUDY: In 130 children monitorized were observed both a large oxacillin exposure in the masculine sex, being used the oxacillin average dose of 216,3mg/kg/day. The accumulative incidence (AI) of AROx was equal to 20,8%, of the total of 3352 patients-day monitorized (incidence density/ ID = 0,8). Of the 43 reactions reports, the most frequent reactions were fever (50%) and cutaneous rash (35,7%). The procedure more used in the case of occurrence of AROx was the suspension of oxacillin use (51,9%). The most of reactions presented causality and gravity as Probable (55,6%) and Moderate (92,6%), respectively. In addition, the average of exposure time to oxacillin and hospitalization time were significantly different between the groups of patients that presented AROx or no. The relative risk (RR) of oxacillin exposure by more than 14 days was 5,46 to AROx occurrence. SECOND STUDY: Of the 76 patients, 36,8% ones related to allergic antecedents. Of these, 72,5% were associated to use of drugs. Oxacillin was considered as first choice drug for treatment of 75% of patients. The association oxacillin plus ceftazidima was the most used (22%) during treatments. The average dose of oxacillin prescribed was 206mg/kg/day. The average time of treatment with oxacillin was 15 days. The ineffective therapeutic (21,1%) and occurrence of adverse reaction (15,8%) caused the suspension of this antibiotic. The permanence time in the hospital of patients was 32,4% (patients-day total: 2463; ID = 0,97). The most frequent reactions were the increase of transaminases (22,1%), fever (17%) and cutaneous rash (13,6%). The majority of reactions showed causality, gravity and hypersensitivity as Probable (44,1%), Moderate (66,1%) and type B (86,4%). The presence of AROx was frequent between patients with age equal or under 14 years old (P = 0,0159)/ RR = 2,22). The incidence of adverse reactions to other medicaments was higher in the AROx patient group (P = 0,0036)/ RR = 2,66). 34% of followed patients presented at least one drug related problem involving oxacillin (DRPOx). A total of 71 DRPOx was identified. Of these DRPOx, the detection of adverse reactions was predominant (33,8%). CONCLUSION: The careful use of oxacillin is recommended in paediatrics, with duration of treatment established promptly. The empirical and prolonged exposure of this drug should be avoided.